2017
DOI: 10.1007/s11837-017-2307-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward Predictive Understanding of Fatigue Crack Nucleation in Ni-Based Superalloys

Abstract: Predicting when and where materials fail is a holy grail for structural materials engineering. Development of a predictive capability in this domain will optimize the employment of existing materials, as well as rapidly enhance the uptake of new materials, especially in high-risk, high-value applications, such as aeroengines. In this article, we review and outline recent efforts within our research groups that focus on utilizing full-field measurement and calculation of micromechanical deformation in Ni-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…al. [30,31,37,38], the effect of neighbouring grains, complex strain path and strain levels can be simulated in mesoscale, to obtain the eventuated plastic strain distribution and the peak value of slip field.…”
Section: Prediction On Dbsmentioning
confidence: 99%
“…al. [30,31,37,38], the effect of neighbouring grains, complex strain path and strain levels can be simulated in mesoscale, to obtain the eventuated plastic strain distribution and the peak value of slip field.…”
Section: Prediction On Dbsmentioning
confidence: 99%
“…On top of this, there is also the issue that any microscopy technique will only capture a tiny fraction of the sample. It has been calculated for example that it would take a billion years to study the volume of material contained within a little finger by TEM [11]. By default, this means one is likely to miss important details, or know whether the image presented is representative of the sample for example.…”
Section: How Does Drying Affect the Networkmentioning
confidence: 99%
“…Dave J. Adams thanks the EPSRC for a Fellowship (EP/L021978/1). Dave J. Adams also thanks Ben Britton for providing the details of reference [11] via Twitter.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This provides the possibility of predicting crack nucleation, using a combination of a damage evolution rule and a criteria based on the stress/strain of components and microstructural length scale associated with the storage of dislocations. The SED criterion has been used various studies [33,34] to predict fatigue crack nucleation. It has been revealed that the stored energy is a good indicator of fatigue crack initiation.…”
Section: Prediction Of Fatigue Crack Initiation Using the Sed Criterionmentioning
confidence: 99%